Embracing business sustainability through innovation and creativity in the service sector - Tyagi, Pankaj Kumar 1979-; Nadda, Vipin 1970-; Bharti, Vishal; Kemer, Ebru (IGI Global, 2023)
This book provides an in-depth understanding of various dimensions of business sustainability through innovation and creativity in the service sector
Keywords: Service industries -- Technological innovations; Service industries -- Environmental aspects; Sustainable development; Aufsatzsammlung